Pengembangan Sistem Informatika Angkutan Lintas Batas Negara (Sisinfo ALBN) Ditjen Perhubungan Darat - Yasmi Afrizal (Rekayasa Sipil, 2013)
The development of the cross border increased economic activity that encourages the economy of transportation as a support tool. Cross-border transport is becoming an essential element of border areas that require monitoring and implementation. Transboundary Information System (SISINFO ALBN) is one of the systems can provide a solution of cross-boder transportation and generates an output useful information to Directorate General of Land Transportation and Cross-border check point such as transportation serving, bus statistics, rates, routes, and so on. Transboundary Information System was developed to provide information the interface which an attribute information transportation. Users can use the access attribute information more presentatif, informative, and interactive way to obtain the information provided by the system.